Pengaruh Modal Sosial terhadap Tingkat Kesejahteraan Rumah Tangga Petani Bawang Merah di Kabupaten Nganjuk - Purbowo Purbowo; Ika Puspitasari Dyah Rahmadhani (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
The dynamics of the agricultural sector's contribution to Indonesia's GDP fluctuate annually, with an increase of 13.70% in 2020 but a decrease in 2021 and 2022 13.28%. This study aims to analyze the relationship between social welfare influenced by social capital in the form of trust, networks, and norms. Research data used a mixed method, a combination of quantitative and qualitative data, conducted by primary data and analyzed each other separately. The multiple linear regression test analyzed quantitative data, while qualitative data was described in-depth. The research instrument used a questionnaire consisting of five Likert scales as a measurement for each variable and interviews to look more deeply at the relationship between social capital and social welfare. The data was determined purposively to shallot farmers in four sub-districts, Gondang, Rejoso, Sukomoro, and Bagor, considering that the highest shallot production was in that area. The data was tested for validity and reliability, and then multiple linear regression tests and classical assumption tests were continued. The results show that trust has no significant effect on farmers' welfare. The same thing also happened to the norm, which did not significantly influence farmers' welfare partially. However, it is different with networks that partially influence the welfare of shallot farmers. Simultaneously, trust, norms, and networks influence the welfare of shallot farmers. The implication of this research is designing an empowerment program that focuses on strengthening social capital among shallot farmers, such as a training program for young farmers as farmers group union (Gapoktan) facilitators and the preservation of independent field extension officers (PPL swadaya) from local farmers to provide knowledge to farmers around them.